Intracranial neuromodulation for pediatric drug-resistant epilepsy: early institutional experience - Uchitel, Julie; Lui, Austin; Knowles, Juliet; Parker, Jonathon J.; Phillips, H. Westley; Halpern, Casey H.; Grant, Gerald A.; Buch, Vivek P.; Hyslop, Ann; Kumar, Kevin K. (Frontiers in Surgery, 2025)
IntroductionPediatric drug-resistant epilepsy (DRE) is defined as epilepsy that is not controlled by two or more appropriately chosen and dosed anti-seizure medications (ASMs). When alternative therapies or surgical intervention is not viable or efficacious, advanced options like deep brain stimulation (DBS) or responsive neurostimulation (RNS) may be considered.ObjectiveDescribe the Stanford early institutional experience with DBS and RNS in pediatric DRE patients.MethodsRetrospective chart review of seizure characteristics, prior therapies, neurosurgical operative reports, and postoperative outcome data in pediatric DRE patients who underwent DBS or RNS placement.ResultsNine patients had DBS at 16.0 ± 0.9 years and 8 had RNS at 15.3 ± 1.7 years (mean ± SE). DBS targets included the centromedian nucleus of the thalamus (78% of DBS patients), anterior nucleus of the thalamus (11%), and pulvinar (11%). RNS placement was guided by stereo-EEG and/or intracranial monitoring in all RNS patients (100%). RNS targets included specific seizure onset zones (63% of RNS patients), bilateral hippocampi (25%) and bilateral temporal lobes (12%). Only DBS patients had prior trials of ketogenic diet (56%) and VNS therapy (67%). Four DBS patients (44%) had prior neurosurgical interventions, including callosotomy (22%) and focal resection (11%). One RNS patient (13%) and one DBS patient (11%) required revision surgery. Two DBS patients (22%) developed postoperative complications. Three RNS patients (38%) underwent additional resections; one RNS patient had electrocorticography recordings for seizure mapping before surgery. For patients with a follow-up of at ≥1 year (n = 7 for DBS and n = 5 for RNS), all patients had reduced seizure burden. Clinical seizure freedom was achieved in 80% of RNS patients and 20% had a >90% reduction in seizure burden. The majority (71%) of DBS patients had a ≥50% reduction in seizures. No patients experienced no change or worsening of seizure frequency.ConclusionIn the early Stanford experience, DBS was used as a palliatively for generalized or mixed DRE refractory to other resective or modulatory approaches. RNS was used for multifocal DRE with a clear seizure focus on stereo-EEG and no prior surgical interventions. Both modalities reduced seizure burden across all patients. RNS offers the additional benefit of providing data to guide future surgical planning.